Die waagstuk van Afrikaans (Historia, 2021)
The Afrikaans wager 'The Afrikaans Wager' takes as its point of departure an essay by N.P. van Wyk Louw, the pre-eminent Afrikaans man of letters. His essay 'Die ewige trek' (The eternal trek) published during the Great Trek centenary (1938) argues that there was a 'balance in the arguments' at turning points in the development of the Afrikaner 81. N.P. VAN WYK LOUW, Versamelde prosa, vol.1, p. 97. Historia 46(2), November 2001, pp. 477-502. 501.Giliomee people. He discusses three such moments: the Great Trek, the Anglo-Boer War and the decision in 1925 to choose Afrikaans rather than Dutch as a second public language. Louw's emphasis on the irrationality of the choices that were made links up with Thomas Carlyle's perspective that the historian has to depict and gauge chaos. This essay discusses Louw's treatment of the three historical moments and adds two: the introduction of apartheid in the later 1940s and early 1950s and the decision in the late 1980s and early 1990s to surrender of power. The perspective of a balance in the options helps the historian to focus not only on the road travelled but also the one not travelled